1979
DOI: 10.1111/j.1469-8986.1979.tb01463.x
|View full text |Cite
|
Sign up to set email alerts
|

Time of Quarter Effect: An Uncontrolled Variable in Electrodermal Research

Abstract: Does the time of the academic quarter in which a subject participates in an electrodermal habituation study have an effect upon electrodermal response components—e.g., skin conductance level (SCL), skin conductance response (SCR), and spontaneous fluctuation (SF) activity? Four groups of 24 undergraduates (12 males and 12 females each) participated in an habituation session consisting of a 10‐min adaptation period and 15, 5‐sec bursts of 85 dB white noise, during the first, fourth, seventh, or tenth week of an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

1993
1993
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…Only Wenger and Cullen (1962) obtained significant correlations of r ¼ 0.27 between air pressure and SCL for their male participants, and Waters et al (1979) found a corresponding effect in their long-term study. Fisher and Winkel (1979) could not confirm correlations between EDA and air pressure.…”
Section: Other Environmental Conditionsmentioning
confidence: 77%
See 2 more Smart Citations
“…Only Wenger and Cullen (1962) obtained significant correlations of r ¼ 0.27 between air pressure and SCL for their male participants, and Waters et al (1979) found a corresponding effect in their long-term study. Fisher and Winkel (1979) could not confirm correlations between EDA and air pressure.…”
Section: Other Environmental Conditionsmentioning
confidence: 77%
“…However, these differences were relatively small, as were the correlations between SCL and humidity (r ¼ À0.23 for females and r ¼ À0.11 for males). Fisher and Winkel (1979) could not determine any significant connection between EDA and humidity. Waters et al (1979) observed significant connections 72 The dry electrodes used in this study may have contributed to this inconsistency.…”
Section: Other Environmental Conditionsmentioning
confidence: 81%
See 1 more Smart Citation
“…Venables () reported a curvilinear relationship, that is, a negative correlation between SCL and humidity from 54% to 66% but positive correlations below 54% and above 66% relative humidity. No connection between EDA and humidity was found by Fisher and Winkel (). In their Mauritian study, Venables and Christie () obtained age‐dependent correlations between various EDA parameters and humidity.…”
Section: Influences On Electrodermal Recordingmentioning
confidence: 90%
“…Beckman silver-silver chloride electrodes, l cm in diameter, were attached to the dorsal and palmar surfaces of the subject's right band with Beckman adhesive collars to measure skin resistance (Fisher and Winkel 1979;Godkewitsch 1976). Beckman electrode paste served äs the electrolyte.…”
Section: Apparatusmentioning
confidence: 99%